Solar-driven photothermal catalytic CO2 conversion: a review - SABI TAKOU, Daniel (My University, 2024)
t It is highly desirable to seek green and sustainable technologies, such as employing photothermal effects to drive energy catalysis processes to address the high energy demand and associated environmental impacts induced by the current methods. The photothermocatalysis process is an emerging research area with great potential in efficiently converting solar energy through various catalytic reactions. However, achieving simultaneously high conversion efficiency, cyclability, and durability is still a daunting challenge. Thus, tremendous work is still needed to enhance solar photothermal catalytic conversion and promote its large-scale applications. This review developed the principles of coupling solar photon and thermal fields underlying the photothermal effect, exploration of efficient nanocatalysts, development of optofluidic reactor model, and photothermal synergistic-driven CO2 reduction mechanisms. The ultimate goal was to provide an effective approach that can effectively convert solar energy into photocarriers/hot-electrons and heat, and importantly, can couple them to regulate catalysis reaction pathways toward the production of value-added fuel and chemical energy.
Keywords: Photochemistry; Photothermal; CO2 catalytic; conversion; Nanomaterial; Solar fuels and chemicals